PENGARUH TIPE GRADASI AGREGAT TERHADAP SIFAT BETON ASPAL DENGAN BAHAN PENGIKAT ASPAL PERTAMINA PEN 60/70 DAN ASPAL STARBIT E-55 CAMPURAN AC-WC - Subarkah, Subarkah; Romadhona, Wisnu (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2015)
Pavement earlier damage in Indonesia was generally due to overloading, repetition of traffic loading, and climatic change. To overcome these main factors, the quality of asphaltic concrete need to be improved properly. This research was to know the effect of difference aggregate gradation types on pavement performance using modification bitumen of Starbit E-55 and bitumen Penetration 60/70. Research was conducted in four stages: 1) to determine optimum bitumen content of four mixture types, 2) Marshall standard and immersion tests at each bitumen content of the mixtures, 3) indirect tensile strength test, and 4) analyzing and comparing the results. The research result shows that bitumen starbit E-55 can be used as an alternative binder for asphaltic concrete. The optimum bitumen content of bitumen Starbit E-55 in AC-WC was 5.75% for dense graded and 6.2 % for gap graded. The mixture with bitumen Starbit E-55 was weaker than that of bitumen penetration 60/70 for both dense and gap graded. Immersion test result shows that the index of retained strength of specimen using bitumen Starbit E-55 was more sensitive than that of using bitumen Pen 60/70. Whereas, in term of indirect tensile strength, specimens using bitumen Penetration 60/70 was more sensitive than that of specimens using Starbit E-55.